Analisis faktor yang Berhubungan dengan Kejadian Efek Samping pada Akseptor Putus Pakai IUD/Implant di Kabupaten Mamuju Tengah - Sukardi Saleh; Ashriady Ashriady; Fajar Akbar (JURNAL KEBIDANAN, 2019)
In 1994 the International Conference on Population and Development (ICPD) has changed the paradigm in managing population problems, which was originally oriented to reducing fertility (humans as objects) to prioritizing individual reproductive health by respecting the reproductive rights of each individual (human being as the subject). The problem that occurs is the participation of couples of reproductive age in family planning programs is not yet complete. One problem that needs attention is that there are PUSs who drop out or no longer use contraception. The number of family planning dropouts in Indonesia has increased, from 11.46% in 2008 to 15.09% in 2012. The potential number of Indonesian population in 2015 reaches 300 million if the family planning movement or the number of family planning dropouts increases or does not run as expected. The results of the study (Maskanah, 2009) showed that the higher the incompatibility of contraceptive use (experiencing side effects), the higher the incidence of family planning contraception dropouts.This type of research is quantitative research with a cross sectional study design. Time of study in November 2018. The population is participants who dropped out of IUD/Implant KB in Central Mamuju Regency in 2018 with a population of 32. The study sample was taken using the Total Sampling method.The results showed that there was a relationship between maternal education level, quality of family planning services, and husband support with the incidence of side effects in drop-outs using IUD/Implant in Central Mamuju District. Efforts to increase PLKB coaching are needed for Participants in IUD and Implant KB, especially in the first month after installation. Improving the quality of family planning services, especially in signing informed consent and screening prospective acceptors before being served.Increased IEC to husbands about the importance of family planning that family-based affairs are not merely the matter of the wife.